Pengaruh Latihan Menggunakan Alat Modified Duo Tir terhadap Peningkatan Kemampuan Shooting Petanque Atlet Pelatda NTB - Beny Suprayogi; Mujriah; Sri Erny Muliyani (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2025)
This study aimed to analyze the effect of training using the Modified Duo Tir tool on improving shooting skills among PELATDA NTB petanque athletes in 2024. A quasiexperimental method with a one-group pretest posttest design was used, involving 9 athletes as research participants. Data were collected using shooting skill tests administered before and after the intervention. The normality test results showed that the data were normally distributed, allowing for the use of a paired sample t-test. The statistical analysis revealed a significant improvement in shooting scores (p = 0.000). These findings indicate that training with the Modified Duo Tir is effective in enhancing shooting accuracy, coordination, and athletes’ concentration. Additionally, the toolsupports more efficient training sessions and technical repetitions. Therefore, it is recommended as an alternative training method in the development of petanque athletic performance.